HOW IS THE FEASIBILITY AND READABILITY OF 10TH GRADE ARABIC LANGUAGE AND LITERATURE TEXTBOOK? / BAGAIMANA KELAYAKAN DAN KETERBACAAN BUKU TEKS BAHASA DAN SASTRA ARAB KELAS X? - Salma Azzahra; Mohamad Zaka Al Farisi (Lughawiyah: Journal of Arabic Education and Linguistics, 2023)
This research aims to determine the suitability of Arabic Language and Literature textbooks for 10th grade High School/MA Students with the BSKAP standards, the readability level, and readability level by student grade. This research used the evaluative method. The researchers used content analysis technique and collected data through literature study and document study to analyze the feasibility of textbooks. The method used to determine the readability level was the Raygor’s graph and the fog index. The results of the study indicate that this book is suitable for use with an overall score of 92.42% which includes aspects of the feasibility of standard content, presentation, design and graphics. However, based on the results of Raygor's graphic analysis, this textbook is not appropriate for use at the 10th grade student because none of the eight texts studied correspond to the 10th grade level. Meanwhile, based on the results of the fog index, this textbook is in easy to read category with a score of 3.72. Overall this book is suitable for use in the 10th grade student, but it needs some adjustments to design standards such as selecting interesting illustrations. Even though it has a high level of feasibility, the readability of this book is not up to the 10th grade student and the readability level is not ideal, so it needs improvement.